Dysregulated circulating microRNA‐126 in chronic obstructive pulmonary disease: linkage with acute exacerbation risk, severity degree, and inflammatory cytokines. Issue 3 (21st January 2022) - Wang, Congying; Feng, Dong; Dong, Shanfeng; He, Ruilian; Fan, Bosheng
Abstract: Background: MicroRNA‐126 (miR‐126) is engaged in respiratory diseases via regulating airway tissue injury and pulmonary inflammation, while its relation with chronic obstructive pulmonary disease (COPD) is not reported. The study aimed to evaluate the value of miR‐126 for estimating COPD acute exacerbation risk and its relation to disease severity and inflammatory cytokines in COPD patients. Methods: This study was a case–control study. Seventy acute exacerbation COPD (AECOPD) patients, 70 stable COPD (SCOPD) patients, and 70 healthy controls (HCs) were consecutively recruited. Plasma miR‐126 expression was detected by reverse transcription quantitative polymerase chain reaction. Plasma tumor necrosis factor α (TNF‐α), interleukin‐1β (IL‐1β), interleukin‐6 (IL‐6), and interleukin‐17 (IL‐17) in COPD patients were further determined by enzyme‐linked immunosorbent assay. Results: MiR‐126 was higher in AECOPD patients compared to SCOPD patients and HCs (both P adj < 0.001). Receiver operating characteristic curves revealed miR‐126 distinguished AECOPD patients from SCOPD patients (area under curve (AUC): 0.805, 95%CI: 0.733–0.877) and HCs (AUC: 0.884, 95%CI: 0.829–0.939) and also distinguished SCOPD from HCs (AUC = 0.656, 95%CI: 0.566–0.747). MiR‐126 positively related to GOLD stage in both AECOPD patients ( p < 0.001) and SCOPD patients ( p < 0.001). Furthermore, miR‐126 positively linked with TNF‐α ( p < 0.001), IL‐1β ( p = 0.002), IL‐6 ( p = 0.009), and IL‐17 ( p < 0.001) levels in AECOPD patients; but miR‐126 only positively related to TNF‐α and IL‐17 levels (all p < 0.050), instead of IL‐1β or IL‐6 level (all p > 0.050) in SCOPD patients and HCs. Conclusion: Dysregulated circulating miR‐126 not only relates to COPD susceptibility and its acute exacerbation risk but also links with disease severity and inflammatory cytokines in COPD patients. Abstract : 70 acute exacerbation COPD (AECOPD) patients, 70 stable COPD (SCOPD) patients and 70 health controls (HCs) were consecutively recruited. Their plasma miR‐126 and inflammatory cytokine levels were detected by RT‐qPCR and ELISA, respectively. MiR‐126 was higher in AECOPD patients compared to SCOPD patients and HCs (both p < 0.001). Receiver operating characteristic curves revealed miR‐126 distinguished AECOPD patients from HCs (AUC: 0.884) and SCOPD patients (AUC: 0.805), which also distinguished SCOPD from HCs (AUC = 0.656). MiR‐126 positively related to GOLD stage in AECOPD patients and SCOPD patients (both p < 0.001). Furthermore, miR‐126 positively linked with TNF‐α ( p < 0.001), IL‐1β ( p = 0.002), IL‐6 ( p = 0.009) and IL‐17 ( p < 0.001) levels in AECOPD patients; but the linkage was weaker in SCOPD patients and HCs. Conclusively, miR‐126 shows potency as biomarker for COPD.